Exploring awareness and public perception towards the importance of visual aesthetics for preservation of Permanent Forest Reserve (PFR) in Malaysia - Mundher, Riyadh; Abu Bakar, Shamsul; Maulan, Suhardi; Mohd Yusof, Mohd Johari; Osman, Syuhaily; Al-Sharaa, Ammar; Gao, Hangyu (Multidisciplinary Digital Publishing Institute, 2022)
Malaysia has suffered a significant loss of forest cover over the years, mainly due to logging and land clearance for agriculture activities. Although the forest legislation has long been established and continuously enforced, it was not inclusive enough to protect the local natural resources. This study aims to identify public perception and awareness regarding values and essential aspects that affect the preservation of permanent forest reserves (PFR) in Malaysia. In particular, this study investigated the values of visual aesthetics to promote the preservation of Malaysian PFR within the existing legal framework. Results from the survey revealed that the public strongly perceived ecology and research education as the two most important aspects of preserving Malaysian PFR. The study also confirmed that visual aesthetics are considered a crucial aspect of forest classification and preservation beyond people’s health, safety, recreational, and economy. Interm of PFR functions, aesthetic is aslo the third most important factors after protection and research/education.